UPAYA HUKUM DIPLOMATIK MALAYSIA TERHADAP DIPLOMAT KOREA UTARA DALAM KASUS PEMBUNUHAN KIM JONG NAM DI MALAYSIA MENURUT KONVENSI WINA 1961: MALAYSIA'S DIPLOMATIC LEGAL REMEDY AGAINST NORTH KOREAN DIPLOMAT IN THE CASE OF KIM JONG NAM ASSASSINATION IN MALAYSIA ACCORDING TO THE 1961 VIENNA CONVENTION - Fadhil, Muhammmad Irfan; Notoprayitno, Maya Indrasti (Fakultas Hukum Universitas Trisakti, 2025)
The right of diplomatic immunity has been contained in the 1961 Vienna Convention on Diplomatic Relations to support the performance of diplomats' duties, but the implementation of this right is often not in line with its designation. As the action of Secretary II Hyon Kwang Song, a diplomatic official of the North Korean Embassy in Malaysia who was involved in the murder of the North Korean leader's brother, Kim Jong Nam. Based on that, this research discusses the action of Hyon Kwang Song who abused the right of diplomatic immunity and the juridical effort made by Malaysia and North Korea in resolving this case. The research technique used normative legal research through descriptive secondary materials and deductive inference. The results of the analysis show that Hyon Kwang Song's action is a form of abuse of diplomatic immunity so that Malaysia declares Hyon Kwang Song as persona non grata or a person who is denied existence, but on the other hand North Korea tries to protect Hyon Kwang Song and does not impose any penalty on the diplomat due to political interest. The conclusion is that diplomatic relations are inseparable from political interest and abuse of diplomatic immunity often occurs and political interest influences the settlement of this case which has resulted in the termination of diplomatic relations between Malaysia and North Korea.